Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2020
DOI: 10.2147/jbm.s277541
|View full text |Cite
|
Sign up to set email alerts
|

<p>A Systematic Review of Transfusion-Transmissible Infections Among Blood Donors and Associated Safety Challenges in Pakistan</p>

Abstract: The blood transfusion (BT) system in Pakistan is fragmented, demand-driven and depends on weakly regulated transfusion practices. There is a considerable possibility that transfusion-transmissible infections (TTIs) are contributing to the current epidemic of hepatitis B virus (HBV) and hepatitis C virus (HCV) (affecting 7.4% of the general population) in the country. To study this issue, we conducted a systematic review to identify articles related to TTIs and transfusion safety in Pakistan from January 1, 201… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(4 citation statements)
references
References 30 publications
1
3
0
Order By: Relevance
“…The prevalence of anti-malarial antibodies among blood donors in the current study is 0.7%, which was consistent with the findings of Hoque et al (0.76%) [49]. Meanwhile, a lower prevalence was reported by Ehsan et al in Pakistan (0.11) [50] and Patel et al [46] in Nepal (0.02%). Several studies conducted in Ethiopia (4.1%) [51] and Tanzania (8%) [52] reported high levels of anti-malarial antibodies.…”
Section: Malariasupporting
confidence: 92%
“…The prevalence of anti-malarial antibodies among blood donors in the current study is 0.7%, which was consistent with the findings of Hoque et al (0.76%) [49]. Meanwhile, a lower prevalence was reported by Ehsan et al in Pakistan (0.11) [50] and Patel et al [46] in Nepal (0.02%). Several studies conducted in Ethiopia (4.1%) [51] and Tanzania (8%) [52] reported high levels of anti-malarial antibodies.…”
Section: Malariasupporting
confidence: 92%
“…At least in the small sample of bone marrow samples found positive for malaria, the even rarer numbers lacking parasites on peripheral blood smear suggests that infection of bone marrow without parasitaemia may be the exception. A systematic review of infections among blood donors during 2010 to 2020 in Pakistan found 0.11 % positive for malaria [ 32 ]. It cannot be known if invasion of blood by the Plasmodium is usually attended by infection bone marrow, the similarities of those rates of infection of blood and bone marrow suggests that may be the case.…”
Section: Discussionmentioning
confidence: 99%
“…This includes inadequate initial screening of donors for high-risk behaviors due to insufficient training of blood bank staff coupled with a lack of universal quality assured serological screening procedures. Additionally, infection control for blood transfusion has been poor, especially in Karachi, where practices depart from infection control standards, especially in reference to waste management, disposal and staff safety [ 51 , 52 ].…”
Section: Discussionmentioning
confidence: 99%